Determination of metals in natural waters, sediments, and soils - Crompton, T. R. (Thomas Roy) (Amsterdam, Netherlands : Elsevier, 2015)
Annotation A comprehensive overview of the various methods available for analysis of metals and a manual for determining metal concentrations in different media such as natural waters, waste waters, sediments and soils. After a discussion of sampling techniques and preservation, it covers metals in rivers and surface ground and mineral waters as well as metals in aqueous precipitation. It also includes detailed information on analysis of metals in sediments, providing a foundation for informed action by environmental interest groups and regulators and a starting point for further study by graduate students, professionals and researchers.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Water -- Analysis; Metals; TECHNOLOGY & ENGINEERING / Environmental / General; Metals; Water -- Analysis; Electronic books; Electronic books